Ação rescisória - Oliveira, Gisele Moraes Melo de (2011)
The action rescisoria emerged in Brazil through the Regulation 737 of 11.25.1850 (which determines the order of Judgment in Commercial Process). The elements of the sentence null were defined by art. 680 And the art. 681, § 4), determined that such a judgment could be canceled through action rescisoria. The present study aims to demonstrate the chances of inappropriate action rescisoria. Will be dealt with the general aspects of the action rescisoria in civil, such as its regulations, conceptualization, legal nature. Will be dealt with on a case by case basis the assumptions provided for in article 485 of the Code of Civil Procedure and the distinction of action rescisoria between the autonomous actions